Optical fiber impairments compensation in a im-dd system using LMS and MLSE equalization (Revista de Investigaciones Universidad del Quindío, 2015)
Currently, Colombia has started the deployment of fiber-to-the-home (FTTH) technology. It is due to the traffic demand and the new services offered to the end users, taking advantage of the great optical fiber bandwidth.  For FTTH massification, the equipments of optical networks must be of low cost, therefore, IM-DD (intensity modulation with direct detection) systems are still implemented in spite of the advantages of coherent detection systems. However, in IM-DD systems, the transmitted signals are not tolerable to the optical fiber impairments, mainly, the chromatic dispersion, which generates the inter-symbol interference (ISI) in the received signal, increasing the bit error rate (BER). In this paper, an IM-DD system is modeled in Virtual Photonics®(VPI) software. The optical network is modulated in No-Return-to-Zero On-Off-Keying (NRZ-OOK) format, at 40 Gbps, reaching distances of 80 km. Optical fiber impairments compensation is proposed using LMS (LeastMean-Square) algorithm, which uses a training sequence to find the channel coefficients, and MLSE (Maximunlikelihood sequence estimation). These techniques allow a BER reduction and improve the system performance.
Keywords: Equalization; Optical Fiber; Least-Mean-Square (LMS); Maximun-likelihood sequence estimation (MLSE); Bit-error-rate (BER)